Single cell analysis of kynurenine and System L amino acid transport in T cells - Linda V. Sinclair; Damien Neyens; George Ramsay; Peter M. Taylor; Doreen A. Cantrell (Nature Communications, 2018)
Kynurenine is an immunomodulatory aryl hydrocarbon receptor (AHR) ligand. Here the authors show, using a new flow cytometry based method, that kynurenine needs to be transported across the plasma membrane of activated T cells by the transporter protein SLC7A5 to activate the AHR.